Characteristics and Prognosis of Patients With Inflammatory Bowel Disease During the SARS-CoV-2 Pandemic in the Basque (2020)
Since the first description of the new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the infection produced by this microorganism (COVID-19) has been confirmed in 1,469,544 individuals around the world (www.healthmap.org/covid-19/). In Spain, the first case of COVID-19 was reported on the January 31, 2020, and currently there are 146,690 confirmed cases and 14,555 deaths secondary to this infection (Ministry of Health, Consumer Affairs and Social Welfare, April 7, 2020). In the Basque Country (Spain), 9452 subjects have a positive test for SARS-CoV-2 (April 7, 2020). Patients with inflammatory bowel disease (IBD) are of special interest during this outbreak because of the high proportion of them taking immunomodulators or biologics. There is also a possible increased risk of viral infections, especially in those receiving thiopurines.1,2 Our aim was to describe the characteristics of patients with IBD with a positive test for SARS-CoV-2, including the course of the infection in terms of medical therapy, hospital or intensive care unit (ICU) admission, and death.